Clinical and Genetic Analyses of 38 Chinese Patients with Peutz-Jeghers Syndrome. (12th May 2020) - Wu, Bo-Da; Wang, Yong-Jun; Fan, Liang-Liang; Huang, Hui; Zhou, Peng; Yang, Mei; Shi, Xiao-Liu
Abstract : Background. Peutz-Jeghers syndrome (PJS) is a rare autosomal dominant inherited disease caused by a germline mutation in the STK11 gene. It is characterized by mucocutaneous pigmentation, gastrointestinal hamartomatous polyps, and cancer predisposition. Aims. We aimed to summarize the main clinical and genetic features of Chinese PJS patients and assessed the genotype-phenotype correlations. Methods. Thirty-eight patients clinically diagnosed with Peutz-Jeghers syndrome were included in this study from 2016 to 2019. Combined direct sequencing and multiplex ligation-dependent probe amplification tests were used to detect germline heterogeneous STK11 mutations. RNA sequencing was performed in polyps of PJS patients and control groups to evaluate the difference in expression of STK11 . The genotype-phenotype correlations were calculated by Kaplan-Meier analyses. Results. All 26 probands and 12 affected relatives had germline heterogeneous STK11 mutations among which 8 variants were novel. Individuals with missense mutations had their first surgery and other symptoms significantly later than individuals with null mutations. Conclusion. This study expanded the spectrum of STK11 gene mutations and further elucidated individuals with null mutations of STK11 typically had an earlier onset of PJS symptoms and needed earlier management.